Regeneration Studies in the African Spiny Mouse - Prata, Diogo Filipe Cabrita (2018)
Across the Metazoa, organisms vary in terms of how they respond to injury. The two basic responses are regeneration or fibrotic scarring. While some groups such as axolotls, amphibians and fish show high regenerative capacity, mammals tend to heal wounds by fibrotic scarring. The African Spiny Mouse (Acomys) has been reported to have the capacity of closing 4-mm full thickness wounds in the ear pinna with full regeneration of the original tissue architecture, including dermis, epidermis, cartilage and hair follicles. In contrast, Mus musculus heals the border wounds by fibrotic scarring. Therefore, Acomys and Mus constitute a powerful comparative framework for the study of mammalian regeneration. The goal in this work was to answer two independent questions. First, we asked whether mesenchymal stem cells (MSC) were present in ear tissue of both species and compared their differentiation capabilities in vitro. Primary cell cultures were established from uninjured ears of both species, immune-phenotyped and cultured in vitro in adipocyte, chondrocyte and osteocyte differentiation media. Differentiation was characterized by staining and marker expression. We found that Mus cells tend to differentiate to adipocytes, while Acomys cells tend to differentiate to chondrocytes. Second, we asked whether telomerase was differentially upregulated in Acomys vs Mus in response to wounding. Both species were subjected to ear wounds and allowed to heal or regenerate. Tissues were harvested at different time points and analyzed for TERT expression by RT-qPCR. Our results were inconclusive. This work constitutes a further step in understanding the molecular and cellular mechanisms that distinguish Acomys as an emerging mammalian regeneration model.